Factors Affecting Exclusive Breastfeeding, Using Adaptive LASSO Regression - Maharlouei, Najmeh MD (International journal of community based nursing and midwifery, 2018)
BACKGROUND: Exclusive breastfeeding (EBF) in the first six months of the life can significantly improve maternal and children health, and it is especially important in low- and middle-income countries. We aimed to determine the factors affecting EBF duration in a sample of Iranian infants